3D Printed Osteoblast-Alginate/Collagen Hydrogels Promote Survival, Proliferation and Mineralization at Low Doses of Strontium Calcium Polyphosphate - Shebin Tharakan; Shams Khondkar; Sally Lee; Serin Ahn; Chris Mathew; Andrei Gresita; Michael Hadjiargyrou; Azhar Ilyas (MDPI AG, 2022)
The generation of biomaterials via 3D printing is an emerging biotechnology with novel methods that seeks to enhance bone regeneration. Alginate and collagen are two commonly used biomaterials for bone tissue engineering and have demonstrated biocompatibility. Strontium (Sr) and Calcium phosphate (CaP) are vital elements of bone and their incorporation in composite materials has shown promising results for skeletal repair. In this study, we investigated strontium calcium polyphosphate (SCPP) doped 3D printed alginate/collagen hydrogels loaded with MC3T3-E1 osteoblasts. These cell-laden scaffolds were crosslinked with different concentrations of 1% SCPP to evaluate the effect of strontium ions on cell behavior and the biomaterial properties of the scaffolds. Through scanning electron microscopy and Raman spectroscopy, we showed that the scaffolds had a granular surface topography with the banding pattern of alginate around 1100 cm−1 and of collagen around 1430 cm−1. Our results revealed that 2 mg/mL of SCPP induced the greatest scaffold degradation after 7 days and least amount of swelling after 24 h. Exposure of osteoblasts to SCPP induced severe cytotoxic effects after 1 mg/mL. pH analysis demonstrated acidity in the presence of SCPP at a pH between 2 and 4 at 0.1, 0.3, 0.5, and 1 mg/mL, which can be buffered with cell culture medium. However, when the SCPP was added to the scaffolds, the overall pH increased indicating intrinsic activity of the scaffold to buffer the SCPP. Moreover, cell viability was observed for up to 21 days in scaffolds with early mineralization at 0.3, 0.5, and 1 mg/mL of SCPP. Overall, low doses of SCPP proved to be a potential additive in biomaterial approaches for bone tissue engineering; however, the cytotoxic effects due to its pH must be monitored closely.